Tingkat Kepuasan Petani Terhadap Kinerja Pelayanan Penyuluhan Pertanian di Desa Karang Sidemen - Sahidu, Arifuddin; Hayati, Hayati; Muktasam, Muktasam; Valentino, Niechi; Hadi, Muhammad Anwar (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Extension workers play a crucial role in the strategic agricultural sector. This study aims to: (1) Describe extension services based on farmers' perceptions of importance and performance, (2) Examine the performance of agricultural extension service attributes from the perspective of farmers' satisfaction in Karang Sidemen Village, Batu Kliang Utara Subdistrict, (3) Provide solutions to improve farmers' satisfaction by enhancing the quality of extension workers' performance. A descriptive-exploratory approach was employed, using surveys, interviews, and questionnaires with quota sampling, involving 4 respondents per farmer group (chairpersons and active members). Data were analyzed using Importance Performance Analysis (IPA). Results indicate that the performance of extension workers in Karang Sidemen Village is relatively satisfactory, with an average score of 3.1. However, farmers' expectations exceed the performance delivered, with a positive comparison score of 1.217 out of 5.0. This underscores the need to improve extension service quality to better meet farmers' expectations.